ANALYZING THE INFLUENCE AMONG CULTURAL FACTOR, SOCIAL AND PSYCHLOGICAL WITH THE CUSTOMER BUYING DECISION OF ORIFLAME PRODUCT IN MANADO - Sanger, Yunita Melani; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Consumer decision in buying products is an important activity in which where all revenues are coming from. The higher degress of product variety is also an influencial aspect in consumer decision for purchasing. The objective of this research is to find out the influence of Cultural, Social and Psychological factors toward consumer decision making for Oriflame product in Manado. This research used the Multiple Regresion Method. The findings showed that the three factors are simultaneously influence toward consumer decision for Oriflame product. Only Social factor has an influence, partially, toward consumer decision, while the Cultural and Psychological needs to increase the quality of cultural and psychological factor, so as to improve the marketing approval to increase the Service Quality for consumer and future sales. Keywords: cultural factor, social factor, psychological factor, customer buying decision